Third-order dispersion compensation for petawatt-level lasers employing object-image-grating self-tiling. (October 2015) - Li, Zhaoyang; Rao, Daxing; Leng, Yuxin; Chen, Lei; Dai, Yaping
Abstract: A method is proposed for third-order dispersion compensation in compressors of femtosecond petawatt laser facilities employing object-image-grating self-tiling technology to prevent the return of the laser beam in amplifying chains. Simulations are performed for functioning and being developed Nd : glass and Ti : sapphire petawatt-level lasers.